From dysfunctional to functional corruption: the politics of decentralized electricity provision in Lebanon. (April 2022) - Ahmad, Ali; McCulloch, Neil; Al-Masri, Muzna; Ayoub, Marc
Abstract: Dysfunctional and corruption-prone power sectors are a persisting challenge in many developing countries. Drawing from the theoretical framework about corruption from Khan, Andreoni and Roy [1] and applying it to electricity, this paper explores the service provision model of Electricite du Zahle (EDZ), a decentralized local utility in Lebanon. Our analysis shows that although EDZ has succeeded in improving the service experienced by its customers, its approach has not reduced corruption. However, despite its deviation from the "standard" model of power sector reform, the EDZ model has achieved a notable developmental outcome in a way that is consistent with the complex political settlement of the country. Our findings point to the possibility of extending similar – second-best, but politically feasible – approaches throughout Lebanon and, potentially, in many other countries where the implementation of centralized power sector reforms has not succeeded.